(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
This laboratory study was carried out to test the effect of the extracts of ethanol, chloroform, volatile oil and emulsifier of Cymbopogon citratus in killing the adults of the thrips tabaci. The concentrations 250, 500 and 1000 ppm. The results showed that the highest percentage of killed in Volatile oil with a concentration of 1000 ppm at 60.00, 63.33, 66.66, 70 and 76.66% for the first, second, third, fifth and seventh days of control and the lowest percentage was for the emulsifier at 30.00, 36.66, 46.66, 53.33 and 63.33% for the first and second, third, fifth and seventh days of the control, respectively, and we noticed that the higher the concentrations, the higher the percentage of killings and the increase in the percentage of killings cumulatively, as it was the highest percentage of killing on the seventh day.